Unveiling the bacterial microbiota profiles across the gastrointestinal tract regions in dairy buffaloes (Bubalus bubalis) - Phoebe Lyndia T. Llantada; Midori Umekawa; Shuichi Karita (Veterinary Integrative Sciences)
Understanding the pivotal role of bacterial communities in the gastrointestinal tract (GIT) of agriculturally significant animals, such as buffalo, on host productivity and health is crucial. However, our knowledge of buffalo GIT bacterial communities remains limited. This study aimed to profile and compare bacterial communities across three distinct GIT regions—forestomach (rumen, reticulum, omasum, abomasum), small intestine (duodenum, jejunum, ileum), and large intestine (cecum, colon, rectum)—in two riverine-type buffaloes using the Illumina MiSeq platform. Fresh samples were collected in triplicate from various GIT sites within two dairy buffaloes reared under identical conditions. Genomic DNA was extracted, and bacterial profiles were analyzed, with sequences annotated using the Green Gene database. The results revealed substantial intra-buffalo variation at lower taxonomic levels, with Bacteroidetes dominating the forestomach and duodenum, while Firmicutes prevailed in the hindgut from the jejunum to the rectum. Comparisons of GIT sites across different buffaloes indicated variations in primary bacterial phyla, with significant taxonomic differences among gut sections in distinct regions but similarities within the same region. This research provides insights into complex microbial communities within the buffalo GIT, contributing to our understanding of buffalo health and productivity.